Does Nurse Case Management Improve the Health Care Outcomes of Patients with Non-Communicable Diseases (NCDs)! - A Narrative Review - Kisokanth, G.; Prathapan, S.; Indrakumar, J.; Joseph, J. (My University, 2015)
Purpose: Nurses play a major role in providing support to individual patients with long term illnesses. However, it is notable that the effectiveness of nurses providing care in improving the health outcomes on patients with chronic diseases is scarce. The purpose of this review is to present the findings and appraisal of the evidences for Nurse case management in improving health outcomes in patients with Type 2 Diabetes Mellitus (DM), Coronary Heart Disease (CHD), Chronic Obstructive Pulmonary Diseases (COPD) or Cancer. Method: A review of the literature published on Nurse case management was performed. A number of 20 literature articles were analyzed. It included studies conducted in different parts of the world between 1994 and 2014 in English. The findings of the researches were tabulated and the rates of effectiveness were analyzed. Results: Significantly positive results were shown in the studies which evaluate the Nurse case management with regard to health outcomes in common non-communicable diseases such as successful self-management of disease, increased functional status, mental improvement and risk reducing behaviors. Conclusion: Overall, this review shows that the Nurse case management provided for the population with Non-communicable diseases such as DM, CHD, COPD and cancer significantly enhances the quality of life of individuals.
Keywords: Nurse case management; Effectiveness; Diabetes mellitus; Chronic obstructive pulmonary diseases; Coronary heart disease; Cancer